Light polyolefin electromagnetic shielding foam material and preparation method thereof

Based on the traditional method of suppressing foaming forming methods, the use of multi -wall carbon nanotubes and functional treatment is used to prepare light polyolefin electromagnetic shielding foam materials to solve the uncomfortable and corrosion resistance of the existing electromagnetic shielding materials The problem achieves the effect of controlling density and excellent electromagnetic shielding performance.

CN119331328APending Publication Date: 2025-01-21CHANGZHOU SHENGYUAN NEW ENERGY MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411455873.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials are bulky, have poor corrosion resistance, poor processing performance, and are costly, making it difficult to effectively solve the problem of electromagnetic pollution.

Method used

The light polyolefin electromagnetic shielding foam material is used to innovative design on the basis of traditional suppression of foaming molding methods, and multi -wall carbon nanotubes and functional treatment are used to prepare electromagnetic electromagnetic with controlling density and low conductive fillers. Shielding foam material.

Benefits of technology

A foam material with light quality, lower density, and excellent electromagnetic shielding performance, reducing the use of conductive fillers, improving production efficiency, and good buffer performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331328A_ABST
    Figure CN119331328A_ABST
Patent Text Reader

Abstract

The invention discloses a light polyolefin electromagnetic shielding foam material and a preparation method thereof. The material comprises polyolefin, a foaming agent, a foaming accelerator, a cross-linking agent and a functional filler. According to the material preparation method, on the basis of traditional pressing foaming forming, the forming process is innovatively designed. According to the light electromagnetic shielding foam material prepared by the preparation method, internal foam holes of the material are open, and the functional filler is distributed in a net shape. The material density is less than 0.29 g / cm < 3 >; the rebound rate is greater than 10.0%; and after compression for 22 hours, the compression set is less than 27.0%. The electromagnetic shielding effectiveness (SE) of the material with the thickness of 2.5 mm at the wave band of 8.2-12.4 GHz (X wave band) can be greater than 35.0 dB. The material can be used for electronic equipment, medical instruments and other products, electromagnetic interference can be prevented, damage to the products in the transportation process can be reduced due to the fact that the foam material has the good buffering performance, and the dual protection effect on the products is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and specifically discloses a lightweight polyolefin electromagnetic shielding foam material and a preparation method thereof. Background Art

[0002] With the development of science and technology, more and more electronic and electrical equipment are applied to various fields of people's lives and work. However, the widespread use of electronic and electrical equipment has brought convenience to people, but it has also made the electromagnetic pollution of the modern social environment more and more serious. According to research, long-term exposure to electromagnetic radiation will cause certain harm to human health. Traditional metal conductors and ferromagnetic electromagnetic shielding materials are bulky, have poor corrosion resistance, are not easy to process and form, have high costs, and will cause secondary pollution of electromagnetic waves, causing harm to workers exposed to electromagnetic radiation. Therefore, it is urgent to develop high-performance electromagnetic shielding materials.

[0003] Compared with traditional metal materials, conductive polymer materials have the advantages of light weight, easy processing, corrosion resistance and greatly adjustable performance. They have become new electromagnetic shielding materials with great application prospects. Conductive polymer materials are divided into two categories: intrinsic (structural) type and filled composite type. Intrinsic conductive polymer materials have good electrical conductivity and can directly serve as electromagnetic shielding materials. However, on the whole, the processing performance and mechanical properties of conductive polymer materials are poor, which also seriously restricts the practical application of intrinsic conductive polymer materials. Filled composite polymer shielding materials are a type of material that is a blend of polymer materials and conductive fillers. By selecting the type of conductive filler and changing the amount of conductive filler, the performance of the material can be adjusted to produce electromagnetic shielding materials that meet different uses.

[0004] Polyolefin materials have good processing performance, excellent mechanical properties, low price, and a wide range of applications. TMMadhu Kumar et al. mixed low-density polyethylene with an appropriate amount of multi-walled carbon nanotubes and graphene nanosheets conductive fillers and lanthanum ferrite magnetic fillers to prepare an electromagnetic shielding material with a maximum shielding effectiveness of 33.57dB at 10.38GHz. CN 105330947 A discloses an LDPE electromagnetic shielding material and a preparation method thereof. The material uses nickel powder and carbon black as conductive fillers, AC as a foaming agent, and adopts extrusion foaming technology. The electromagnetic shielding effectiveness is as high as 80.0dB. CN 107540959A discloses a multifunctional foam sheet and a preparation method thereof. The foam sheet is made of polyolefin as the main material, and a continuous and dense metal coating is plated on the surface of the material. The density of the prepared foam sheet is less than 0.2g / cm 3 , electromagnetic shielding effectiveness ≥30dB.

[0005] The invention is innovatively designed on the basis of the traditional pressing and foaming molding method. Compared with the traditional pressing and foaming method at a certain temperature and time, the new method can realize the controllable density of the prepared foam material and the lower density. Summary of the invention

[0006] The purpose of the present invention is to provide an electromagnetic shielding material with low conductive filler addition, light weight and excellent electromagnetic shielding performance. The material preparation inherits and innovates the traditional pressing foaming molding method, realizes a new method for preparing electromagnetic shielding foam materials with controllable foaming material density and lower density.

[0007] The present invention is achieved by the following technical means:

[0008] The present invention first discloses a lightweight polyolefin electromagnetic shielding foam material, comprising:

[0009] 100 parts of polyolefin, 2-10 parts of foaming agent, 1-5 parts of foaming accelerator, 0.2-1 parts of cross-linking agent, 1-10 parts of functional filler.

[0010] Furthermore, the polyolefin is selected from one or two of the following:

[0011] Density: 0.880-0.930g / cm 3 , low density polyethylene (LDPE) with a melt index of 3.0-12.0 g / 10min;

[0012] Density: 0.918-0.935 g / cm 3 , linear low-density polyethylene (LLDPE) with a melt index of 4.0-8.0 g / 10 min;

[0013] Density: 0.928-0.948 g / cm 3 , ethylene-vinyl acetate copolymer (EVA) with a melt index of 5.0-15.0 g / 10 min, and a vinyl acetate (VA) content of 15.0-45.0%.

[0014] The VA content in the selected EVA can be determined according to the properties of the prepared material. EVA with a high VA content is closer to the properties of rubber.

[0015] Furthermore, the foaming agent is selected from the following:

[0016] Melting point 220-225℃, density 1.65g / cm 3 Azodicarbonamide;

[0017] Melting point 160-161℃, density 1.494g / cm 34,4'-di-sulfonylhydrazide diphenyl ether.

[0018] Further, the foaming promoter is selected from a mixture of zinc oxide and stearate;

[0019] The stearates include calcium stearate, zinc stearate and barium stearate.

[0020] Foaming promoters can reduce the decomposition temperature of foaming agents, allowing polyolefins to be foamed at lower temperatures. The foaming temperature cannot be too high. If the foaming temperature is too high, on the one hand, the polyolefin is prone to degradation due to high temperature, and on the other hand, the melt viscosity of the polyolefin becomes low due to high temperature, and the gas generated by the decomposition of the foaming agent is easy to escape from the melt, affecting the foaming effect of the material.

[0021] Furthermore, the cross-linking agent is selected from one or two of the following:

[0022] Dibenzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, diisopropylbenzene peroxide.

[0023] The cross-linking agent can cross-link polyolefins and increase the viscosity of the melt to reduce the escape of the gas from the decomposition of the foaming agent from the melt, which is beneficial for the material to form a dense foam.

[0024] Furthermore, the functional filler is selected from one or two of the following:

[0025] Purity>95.0%, diameter 20-40nm, density 1.8-2.1g / cm 3 of carbon black;

[0026] Single-walled carbon nanotubes with a purity of >97.0% and a diameter of 1-2 nm;

[0027] Double-walled carbon nanotubes with a purity of >60% and a diameter of 2-4 nm;

[0028] Purity>98.0%, tube diameter 4-8nm, density 2.1g / cm 3 of multi-walled carbon nanotubes.

[0029] Furthermore, the functional filler has a purity of >98.0%, a tube diameter of 4-8nm, and a density of 2.1g / cm 3 of multi-walled carbon nanotubes.

[0030] Since carbon nanotubes themselves have the phenomenon of aggregation and entanglement, which is not conducive to industrial application, multi-walled carbon nanotubes need to be functionalized. After the treatment, the carbon nanotubes are shortened, dispersed more evenly, the dispersion is improved, and the opening rate is also greatly improved.

[0031] The present invention also discloses a method for preparing any of the above-mentioned lightweight electromagnetic shielding foam materials, comprising:

[0032] (1) Preparation of a mixed material: uniformly mixing polyolefin, functional filler, foaming agent, foaming promoter, and cross-linking agent to obtain a first material for later use;

[0033] (2) Preparation of lightweight electromagnetic shielding foam material: The first substance is crushed and placed into a mold on a press plate for foaming. After 15 minutes, the mold is opened, the pressure is quickly released, and the material is cooled to obtain a lightweight electromagnetic shielding foam material.

[0034] Furthermore, the mixing temperature in step (1) is 120°C.

[0035] Furthermore, the functional filler in step (1) needs to be functionalized before use.

[0036] Furthermore, in step (2), the foaming molding temperature is 185° C. and the pressure is 10.0-18.0 MPa.

[0037] The polyolefin light electromagnetic shielding foam material prepared by the invention has open pores, and multi-walled carbon nanotubes are distributed on the pore walls. When the gas expands rapidly, the multi-walled carbon nanotubes are oriented on the pore walls, and the multi-walled carbon nanotubes form an interconnected network structure inside the material.

[0038] The invention also discloses a mold for preparing lightweight polyolefin electromagnetic shielding foam material. The mold is innovatively designed based on the traditional mold, and springs are respectively installed at the four corners of the male and female molds of the mold. This design is the key to preparing lightweight electromagnetic shielding foam material.

[0039] The beneficial effects of the present invention are:

[0040] Compared with the traditional compression foaming molding, the new compression foaming molding method of the present invention does not need to wait for the polymer melt to cool and set before opening the mold, but directly opens the mold (i.e., quickly releases the pressure), and the gas dissolved in the melt expands rapidly, and the melt completes cooling and setting during the expansion process, which greatly shortens the setting time of the product and improves production efficiency. The new compression foaming molding method of the present invention can control the speed of mold opening (i.e., the speed of pressure relief) by adjusting the spring coefficient between the molds, thereby controlling the density of the foaming material, so the new compression foaming molding method can produce foaming materials of different densities. In particular, it can produce foaming materials with lower density than the traditional compression foaming molding method. The electromagnetic shielding material produced by the new compression foaming molding method of the present invention achieves the same shielding effectiveness as the traditional molding method, and requires less conductive filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1This is a schematic diagram of the main structure of the mold for the new compression foaming molding method.

[0042] Figure 2 The shielding effectiveness of the embodiments and comparative examples in the X-band.

[0043] Figure 3 The morphological structures of the embodiments and comparative examples are SEM images, where: (a) Embodiment 1; (b) Embodiment 2; (c) Embodiment 3; (d) Embodiment 4; (e) Embodiment 5; and (f) Comparative Example 2.

[0044] Figure 4 It is a traditional compression foaming mold.

[0045] Figure 5 It is the compression foaming molding die of the present invention. DETAILED DESCRIPTION

[0046] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment. The mold main structure of the present invention is as follows Figure 1 shown. Figure 4 It is a traditional pressing foaming mold. Figure 5 This is an innovatively designed mold of the present invention. The newly designed mold mainly has springs installed on the four guide columns of the mold, so that when the mold is opened, the female mold and the male mold can be quickly separated under the elastic force of the spring. When the newly designed mold is used for compression foaming, the pressure is released and the mold is opened after a certain period of time under a certain pressure. Due to the action of the spring, the male mold and the female mold are quickly separated, the pressure of the melt in the mold drops suddenly, and the gas dissolved in the melt expands rapidly, so that a low-density foaming material can be prepared. By using springs with different elastic coefficients, the speed of mold opening can be adjusted, thereby preparing foaming materials with different low densities.

[0047] The test methods used for the various properties of the lightweight polyolefin electromagnetic shielding foam material of the present invention are as follows:

[0048] Density: Comply with GB / T 1033 standard.

[0049] Mechanical properties: comply with GB / T 9641 standard.

[0050] Volume resistivity: Comply with GB / T 1410-2006 standard.

[0051] Electromagnetic shielding effectiveness: The shielding effectiveness of the sample was tested using a vector network analyzer (produced by Agilent, USA, model N5230A) using the coaxial transmission reflection method. The test frequency range was 8.2-12.4 GHz. The sample was a disc with a thickness of 2.5 mm and a diameter of 13.0 mm.

[0052] Rebound rate: comply with GB / T 6670-1997 standard.

[0053] Compression set: Execute GB / T 6669-20087 standard

[0054] Morphological structure: First, the sample was cooled with liquid nitrogen to make it brittle, and then a scanning electron microscope (SEM) was used to observe the cross-sectional morphology of the sample.

[0055] Example 1

[0056] Functionalization of multi-walled carbon nanotubes (brand: TNIM4, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences): The steps are as follows:

[0057] (1) 10.0 g of multi-walled carbon nanotubes were placed in 1600 ml of concentrated mixed acid, which was a mixture of concentrated nitric acid and sulfuric acid in a volume ratio of HNO3:H2SO4=1:3. The mixture was heated to reflux at 150°C for 24 h, then filtered and washed with distilled water until neutral, dried, and finally subjected to high-speed ball milling for 3 h to obtain functionalized carbon nanotubes.

[0058] (2) Preparation of lightweight polyolefin electromagnetic shielding foam material: 100.0 parts of LDPE (Sinopec Yanshan Petrochemical Company, brand: LD100-AC) were melted on a double-roll mill by weight, the distance between the two rollers was adjusted to 1.2 mm, the temperature was 120.0°C, and after the LDPE was melted and adhered to the rollers, 6.0 parts of multi-walled carbon nanotubes, 4.0 parts of AC, 0.8 parts of DCP, 0.8 parts of zinc oxide and 1.2 parts of barium stearate were added respectively. After mixing for 10.0 minutes, the uniformly mixed material was unloaded from the rollers to obtain a mixture. The mixture was then crushed, and then a certain amount of the crushed material was weighed and put into the mold on the press plate for foaming molding at a temperature of 185.0°C and a pressure of 10.0-18.0 MPa. After 15.0 minutes, the mold was opened, and the female mold and the male mold were quickly opened under the action of the spring, and the melt in the mold was quickly depressurized and expanded, and cooled to obtain a lightweight polyethylene electromagnetic shielding foam material. The electromagnetic shielding effectiveness (SE) of the material is as follows: Figure 2 The cross-sectional morphology of the material is as follows: Figure 3 The specific composition and other properties of the materials are shown in Tables 1 and 2.

[0059] Table 1 Raw material composition of the embodiments and comparative examples

[0060] Raw material composition Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 LDPE 100.0 80.0 80.0 80.0 80.0 100.0 80.0 EVA 0.0 20.0 20.0 20.0 20.0 20.0 20.0 MWCNT 6.0 2.0 6.0 9.0 6.0 6.0 6.0 DCP 0.8 0.8 0.8 0.8 0.8 0.0 0.8 AC 4.0 4.0 4.0 4.0 6.0 0.0 4.0 ZnO 0.8 0.8 0.8 0.8 0.8 0.0 0.8 ZnS 1.2 1.2 1.2 1.2 1.2 0.0 1.2

[0061] Table 2 Performance of Examples and Comparative Examples

[0062]

[0063] *SE is the maximum value of polyolefin shielding material in the X-band.

[0064] Example 2

[0065] Preparation of lightweight polyolefin electromagnetic shielding foam material: 80.0 parts of LDPE (Sinopec Yanshan Petrochemical Company, brand: LD100-AC) and 20.0 parts of EVA (Taiwan Plastics, brand: 750H; VA content: 19.0%) were melted on a double-roll mill, the distance between the two rollers was adjusted to 1.2 mm, the temperature was 120.0°C, and after LDPE and EVA were melted and adhered to the rollers, 2.0 parts of functionalized multi-walled carbon nanotubes, 4.0 parts of AC, 0.8 parts of DCP, 0.8 parts of zinc oxide and 1.2 parts of barium stearate were added respectively. After mixing for 10.0 minutes, the uniformly mixed material was unloaded from the roller to obtain a mixed material. The mixed material was then crushed, and then a certain amount of the crushed material was weighed and put into the mold on the press plate for foaming molding at a temperature of 185.0°C and a pressure of 10.0-18.0MPa. After 15.0 minutes, the mold is opened. The female mold and the male mold are opened quickly under the action of the spring. The melt in the mold is quickly decompressed and expanded, and then cooled to obtain a lightweight polyethylene electromagnetic shielding foam material. The electromagnetic shielding effectiveness (SE) of the material is as follows: Figure 2 The cross-sectional morphology of the material is as follows: Figure 3 The specific composition and other properties of the materials are shown in Tables 1 and 2.

[0066] Example 3

[0067] The preparation method of the lightweight polyolefin electromagnetic shielding foam material is the same as that of Example 2, but the material composition is different, as shown in Table 1. The electromagnetic shielding effectiveness (SE) of the material is as follows Figure 2 The cross-sectional morphology of the material is as follows: Figure 3 The other properties of the material are shown in Table 2.

[0068] Example 4

[0069] The preparation method of the lightweight polyolefin electromagnetic shielding foam material is the same as that of Example 2, but the material composition is different, as shown in Table 1. The electromagnetic shielding effectiveness (SE) of the material is as follows Figure 2 The cross-sectional morphology of the material is as follows: Figure 3 The other properties of the material are shown in Table 2.

[0070] Example 5

[0071] The preparation method of the lightweight polyolefin electromagnetic shielding foam material is the same as that of Example 2, but the material composition is different, as shown in Table 1. The electromagnetic shielding effectiveness (SE) of the material is as follows Figure 2 The cross-sectional morphology of the material is as follows: Figure 3 Other properties are shown in Table 2.

[0072] The difference between Example 1 and Example 3 is that the former contains only LDPE, while the composition of Example 3 includes LDPE and EVA. Figure 3 It can be found that the pore size of the LDPE foam material containing EVA is more uniform, while the foam material composed of only LDPE has collapsed, resulting in uneven pore size. The difference between Example 3 and Example 5 is that the amount of foaming agent in the latter is increased by 50.0% compared with the former, and the other compositions and contents are exactly the same. From Table 3, it can be found that the tensile strength and compression permanent deformation of the material with a higher content of foaming agent in the composition are lower, and the pore size becomes uneven, such as Figure 3 . The compositions of Example 3, Example 2 and Example 4 are exactly the same, but the contents of multi-walled carbon nanotubes in the three examples are different. The content of multi-walled carbon nanotubes in Example 2 is the lowest, and its electromagnetic shielding effectiveness is the worst, as shown in Table 2. The content of multi-walled carbon nanotubes in Example 4 is the highest, and its electromagnetic shielding effectiveness is not much different from that of Example 3, which shows that when the content of multi-walled carbon nanotubes in 100.0 parts of polyolefin foaming material is 6.0 parts, the multi-walled carbon nanotubes have formed a network structure distribution inside the material, and have good electromagnetic shielding effectiveness.

[0073] Comparative Example 1

[0074] The composition of Comparative Example 1 is the same as that of Example 1 (as shown in Table 1), except that there is no AC, DCP, zinc oxide and barium stearate. The preparation of the mixture is exactly the same as that of Example 1. The difference is the molding of the mixture in the mold. A certain amount of the mixture is weighed and crushed, and placed in the mold on the press plate at a temperature of 185.0°C and a pressure of 10.0-18.0MPa. After cooling, the mold is opened to obtain a polyethylene electromagnetic shielding material. The mold used in Comparative Example 1 is a traditional compression molding mold, and there is no spring between the two molds. The electromagnetic shielding effectiveness (SE) of the material is shown in the figure, and other properties of the material are shown in Table 2.

[0075] From Table 2, it can be found that, in addition to the different compositions, the main difference between Comparative Example 1 and Example 1 is that the former material is not foamed and is a non-foamed material. The latter material is a foamed material. The shielding effectiveness of the two is relatively close, but the other properties are very different. The density and tensile strength of the latter are much higher than the former, and the rebound rate of the latter is slightly lower than the former.

[0076] Comparative Example 2

[0077] The material composition of Comparative Example 1 is exactly the same as that of Example 3 (as shown in Table 1). The preparation of the mixture is exactly the same as that of Example 3. The difference is the molding of the mixture in the mold. A certain amount of the mixture is weighed and crushed, and then placed in the mold on the press plate at a temperature of 185.0°C and a pressure of 10.0-18.0MPa. After cooling, the mold is opened to obtain a polyethylene electromagnetic shielding foam material. The mold used in Comparative Example 2 is a traditional pressing mold, and there is no spring between the two molds. The electromagnetic shielding effectiveness (SE) of the material is as shown in Figure 2 The morphology and structure of the material are as follows: Figure 3 The other properties of the material are shown in Table 2.

[0078] Comparative Example 2 and Example 3 have the same composition, except that the former is prepared by a conventional pressing foaming method, while the latter is prepared by the foaming method of the present invention. As can be seen from Table 2, the shielding effectiveness of the two is not much different, but the density and tensile strength of the latter are much lower than those of the former, while the permanent deformation and rebound rate are higher than those of the former. Figure 3 It can be found that the foam material prepared by the traditional compression foaming method has a smaller pore size and a higher pore density.

[0079] The polyolefin electromagnetic shielding foam material prepared by the present invention is light in weight and has high shielding efficiency per unit density. Compared with the traditional pressing foaming method, the foam material prepared by the present invention has controllable density, lower density, and better electromagnetic shielding efficiency and cushioning performance. It can be used for packaging and transportation of electronic products and medical equipment.

[0080] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will be within the protection scope of the present invention.

Claims

1. A lightweight polyolefin electromagnetic shielding foam material, comprising: 100 parts of polyolefin, 2-10 parts of foaming agent, 1-5 parts of foaming accelerator, 0.2-1 parts of cross-linking agent, 1-10 parts of functional filler.

2. The lightweight polyolefin electromagnetic shielding foam material according to claim 1, wherein: The polyolefin is selected from one or two of the following: Density: 0.880-0.930g / cm 3 , low density polyethylene with a melt index of 3.0-12.0g / 10min; Density: 0.918-0.935 g / cm 3 , linear low density polyethylene with a melt index of 4.0-8.0 g / 10min; Density: 0.928-0.948 g / cm 3 , ethylene-vinyl acetate copolymer with a melt index of 5.0-15.0 g / 10 min and a vinyl acetate content of 15.0-45.0%.

3. The lightweight polyolefin electromagnetic shielding foam material according to claim 1, wherein: The foaming agent is selected from the following: Melting point 220-225℃, density 1.65g / cm 3 Azodicarbonamide; Melting point 160-161℃, density 1.494g / cm 3 4,4'-di-sulfonylhydrazide diphenyl ether.

4. The lightweight polyolefin electromagnetic shielding foam material according to claim 1, wherein: The foaming promoter is a mixture of zinc oxide and stearate; The stearates include: calcium stearate, zinc stearate, and barium stearate; The cross-linking agent is selected from one or two of the following: Dibenzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, diisopropylbenzene peroxide.

5. The lightweight polyolefin electromagnetic shielding foam material according to claim 1, wherein: The functional filler is selected from one or two of the following: Purity>95.0%, diameter 20-40nm, density 1.8-2.1g / cm 3 of carbon black; Single-walled carbon nanotubes with a purity of >97.0% and a diameter of 1-2 nm; Double-walled carbon nanotubes with a purity of >60% and a diameter of 2-4 nm; Purity>98.0%, tube diameter 4-8nm, density 2.1g / cm 3 of multi-walled carbon nanotubes.

6. A method for preparing the lightweight electromagnetic shielding foam material according to any one of claims 1 to 5, comprising: (1) Preparation of a mixed material: uniformly mixing polyolefin, functional filler, foaming agent, foaming promoter, and cross-linking agent to obtain a first material for later use; (2) Preparation of lightweight electromagnetic shielding foam material: The first substance is crushed and placed into a mold on a press plate for foaming. After 15 minutes, the mold is opened, the pressure is quickly released, and the material is cooled to obtain a lightweight electromagnetic shielding foam material.

7. The preparation method according to claim 6, wherein: The mixing temperature in step (1) is 120°C.

8. The preparation method according to claim 6, wherein: The functional filler in step (1) needs to be functionalized before use.

9. The preparation method according to claim 6, wherein: The foaming molding temperature in step (2) is 185° C. and the pressure is 10.0-18.0 MPa.

10. A mold for preparing a lightweight polyolefin electromagnetic shielding foam material, wherein: Springs are installed at the four corners of the male and female molds of the mold.

Citation Information

Patent Citations

  • LDPE electromagnetic shielding material and preparation method thereof

    CN105330947A

  • Multifunctional foam sheet and preparation method thereof

    CN107540959A

Cited By

  • Thermoplastic elastomer-based foaming composite material with excellent conductivity and electromagnetic shielding performance and preparation method thereof

    CN120464051A